Quality of health care in the Lao People's Democratic Republic - John Peabody; Mary Tran; David Paculdo; Azusa Sato; Kirthi Ramesh (Asian Development Bank Institute (ADBI), 2019)
The Lao People's Democratic Republic (Lao PDR) has ambitious and laudable goals for universal health coverage, with a view to increasing health outcomes especially for the most vulnerable in society. It has set up the National Health Insurance Bureau, which covers nearly the entire population, through which out-of-pocket payments have been reduced and access to health care facilities has increased, including utilization. However, the attention given to the quality of care is still less than optimal. Further, while the Lao PDR has existing guidelines and policies for quality, its measurement capacity is still nascent. In particular, work on clinical quality of care is just beginning. This paper outlines the different dimensions of quality (structural, process, outcome), and reports results from data collected from six facilities in Luang Prabang on clinical quality, using vignettes. Findings show that the Lao PDR tends to focus on structural elements of care, such as staffing levels and infrastructure, rather than process measures, which are linked experimentally to better outcomes. Vignettes is a feasible tool to measure quality of care in the Lao PDR, but its methodology needs to be better understood by policy makers. The paper links with current proposed Asian Development Bank projects in the Lao PDR on quality of health care and complementary technical assistance projects.
Keywords: I10; I15; 330; quality of care; Lao People's Democratic Republic; patient outcomes; vignettes